Insights on Climate Risks to the Central African Forest Ecosystems: An Interdisciplinary Review - Laura Burgin; Amy Doherty; Adam Higazi; Katy Richardson; Roger Calow (Climate Resilience and Sustainability)
ABSTRACT The Congo Basin in Central Africa is home to the second largest rainforest in the world after the Amazon. These forests sequester more carbon than any other tropical forest both in the above‐ground biomass and in the world's largest peat deposits, located in the Cuvette Centrale. These ecosystems are important for biodiversity and the livelihoods and wellbeing of local people, and they play a crucial role in local, regional and global water cycles. This interdisciplinary analysis of climate change and biodiversity sciences was used to bring together multiple sources of information to assesses the hazard, exposure and vulnerability dimensions of climate risks to Central Africa's forests and the people who live there. Tailored climate information was developed by integrating multiple sources of climate data and literature reviews. This information was analysed alongside a review of biological diversity in the Congo Basin forests so that climate risks to the functioning of forest ecosystems could be assessed. It is clear that the possible impacts of climate change need to be understood alongside and in terms of interactions with a wide range of anthropic pressures in Central Africa. The ecosystem services of Central Africa's forests are globally essential but face competing pressures and are undervalued in conventional economic terms. Oil and gas exploration is a challenge to global climate change mitigation agreements and to biodiversity. Hunting has led to defaunation in some areas, disturbing ecosystems and threatening iconic species. Unregulated logging and forest clearance for agriculture and oil palm plantations are also major threats to forest ecology and biodiversity. The joint approach of this study demonstrates that integration of expertise is necessary to support climate mainstreaming and to meet the growing demand for evidence to inform protection strategies for biodiverse regions worldwide, particularly in observation sparse areas such as Central African forests.